Association of ALOX5AP gene single nucleotide polymorphisms and cerebral infarction in the Han population of northern China - Zhang Shuang-yan; Xu Mei-ling; Zhang Cui-e; Qu Zheng-yi; Zhang Bin-bin; Zheng Zu-yan; Zhang Li-ming (BMC, 2012)
Abstract Background To explore the association of ALOX5AP single nucleotide polymorphisms (SNPs) and haplotype with the occurrence of cerebral infarction in the Han population of northern China. Methods Blood samples were collected from 236 patients of Han ancestry with a history of cerebral infarction and 219 healthy subjects of Han ancestry with no history of cerebral infarction or cardiovascular disease. Applied Biosystems® TaqMan® SNP Genotyping Assays for SNP genotyping were used to determine the genotypes of 7 ALOX5AP SNP alleles (rs4073259, rs4769874, rs9315050, rs9551963, rs10507391, rs9579646, and rs4147064). Results One SNP allele (A) of rs4073259 was significantly associated with development of cerebral infarction (P = 0.049). In comparison to control groups, haplotype rs9315050&rs9551963 AAAC [OR (95% CI) =1.53 (1.02-2.29)], and genotypes rs4147064 CT [OR (95% CI) =1.872 (1.082-3.241)], and rs9551963 AC [OR (95% CI) = 2.015 (1.165-3.484)] increased the risk of cerebral infarction in patients with hypertension. Genotype rs9579646 GG [OR (95% CI) = 2.926 (1.18-7.251)] increased the risk of, while rs4073259 GG [OR (95% CI) = 0.381 (0.157-0.922)] decreased the risk of cerebral infarction in patients with diabetes. Conclusion These results suggest the ALOX5AP SNP A allele in rs4073259 and genotype rs9579646 GG, rs9551963 AC, and haplotype rs9315050 & rs9551963 AAAC were associated with an increased risk of ischemic stroke in the Han population, while rs4073259 GG was associated with a decreased risk.